Pengembangan E-Modul Edutainment-Sway Pembelajaran Instalasi Tenaga Listrik di SMK Kelas XII Teknik Instalasi Tenaga Listrik - Hendri Masdi; Azry Ram Pratama (Universitas Negeri Padang, 2022)
This study aims to produce a website-based edutainment learning module using Microsoft Sway with the research subject is students from class XII TITL at one of Vocational High School in Batam (SMKS Islam Hang Tuah) in first semester of the 2021/2022 Academic Year. This research is conducted based on research and development (R&D) with a 4D development model. The data analysis is carried out by testing the validity, practicality, and effectiveness of KD 3.11. The validity test of the module has been done by three validators consisting of two lecturers from Department of Electrical Engineering, Universitas Negeri Padang and a teacher from SMKS Islam Hang Tuah an the practicality test of the module is given to a teacher and 24 students from the same school. Meanwhile, the effectiveness test of the module uses an evaluation test given to students after learning with the module. The module validation results are 87.2% with a very valid category obtained from the average score of 3 validators. The score of the practicality of the module by the teacher is in the very practical category and by students in the very practical category. The learning outcomes of students after using the module were 20 students who completed out of 24 students, so that the module can be said to be effective. The results of the study can be concluded that the module is valid, practical, and effectively used for the subject of Electrical Power Installation in XII TITL class of SMKS Islam Hang Tuah Batam.